KEBIJAKAN INSTITUSI PENDIDIKAN DALAM PENGEOLAAN OBESITAS PADA REMAJA - Dana Irnanda (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTObesity is as excess fatty tissue in the adipose tissue, where the limit for obesity is excess weight more than 20% of normal weight. The efforts of prevention and management of obesity in adolecents is currently done with clear activities. The policy of educational institutions to help address the problem of obesity in adolecents. This type of research is qualitative research design study exploratory, using in depth interview data and focus group discussion (FGD). The interview is done to the head of educational authority, the headmaster, sport teacher and students. The place of research includes 3 schools that is SMK 3 Pekanbaru, SMA 4 Pekanbaru and SMA Santa Maria Pekanbaru in June – December 2016 with the interview guidelines. The research results showed that the absence of a special curriculum on obesity but there are health materials in subjects Penjaskes and IPA, not to its optimal implementation of policies related to the provision of meals in school, the absence of specific policies that govern about setting up physical activity, as well as health care policies already in school, but specific policies for obesity is not yet available.Keywords: obesity, policy, curriculum, food provision, physical activity, health services